Klasifikasi Penerima Bantuan Pangan Non Tunai (BPNT) Menggunakan Metode Naïve Bayes Pada Desa Cibentang - Muhamad Irvan Vadilah; Rahmawati (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
BPNT (Non-Cash Food Assistance) is a government assistance program in the form of basic necessities or cash to provide food for beneficiary families (KPM). Cibentang Village, Ciseeng District, Bogor Regency is one of the villages that has an important role in helping the progress of the poverty eradication program programmed by the central government. This research discusses the application of the Naïve Bayes method which will make it easier to design research that aims to describe and explain objects based on existing conditions. The naïve Bayes method will classify some data and will produce a probability that can be used as a reference in the future by calculating the precision and accuracy values obtained from the bpnt data. The Naive Bayes method has been proven to be able to carry out classification with an accuracy level of 54.46%.